Recent seismic status of Shillong Plateau, Northeast India - Panthi, Ananta; Singh, HN (BIBECHANA, 2012)
Seismic status of Shillong Plateau of Northeast India has been studied, considering spatial and temporal pattern of the region and using seismicity data for the period 1808-2008. Cutoff magnitude and b-value has been estimated using earthquake data for the period 1963-2008. Seismic activity is observed to be very feeble along the major faults of Shillong Plateau and strong activity is found to occur slightly away from these faults and confined within middle portion at two locations of the region. The temporal pattern shows that the region is due for great earthquake. Focal depth distribution of the events shows that all the events are intermediate depth (less than 70 km). DOI: http://dx.doi.org/10.3126/bibechana.v9i0.7175 BIBECHANA 9 (2013) 59-62